Transport of statins by human ABC efflux transporters in vitro - Tuomi, Suvi-Kukka (My University, 2021)
Transporters are cell membrane proteins, which mediate the cellular influx or efflux of compounds. Transporters expressed in tissues important for pharmacokinetics, can play a crucial role in drug absorption, distribution and excretion. Statins inhibit 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and are used to treat hypercholesterolemia and to prevent cardiovascular diseases. Statins are usually well-tolerated and most adverse effects are mild. Statin-induced muscle toxicity is generally dose- and concentration-dependent. The inhibition of statin transport can alter statin plasma concentrations and thus the risk of adverse effects. The aim of the study was to characterize the transport of atorvastatin, fluvastatin, pitavastatin, pravastatin and rosuvastatin via ABC efflux transporters, including breast cancer resistance protein (BCRP), P-glycoprotein (P-gp), multidrug resistance-associated protein (MRP) 2-4 and 8 in vitro. Vesicular transport assays were used to investigate statin transport through specific efflux transporters. The transport studies were divided into three parts: screening of statin transport, time-linearity of transport and concentration-dependent transport. The results demonstrated that atorvastatin and pitavastatin are substrates of BCRP, P-gp and MRP3, fluvastatin is a substrate of BCRP, P-gp, MRP2, MRP3 and MRP4, pravastatin is a substrate of MRP3 and rosuvastatin is a substrate of BCRP, P-gp and MRP4 in vitro. Simvastatin acid was not transported by any of the studied transporters. This thesis improves general understanding of pharmacokinetic properties of atorvastatin, fluvastatin, pitavastatin, pravastatin and rosuvastatin. These data are useful in predicting the effects of transporter-mediated drug-drug interactions and genetic variability in transporter function on the pharmacokinetics, efficacy and safety of statin therapy.
Keywords: Efflux transporter, statin, concentration-dependent transport